El embargo castigado: consideraciones (ya) inactuales sobre un viejo problema tratado de superar con el VII Pleno Casatorio Civil (Sentencia de Casación No. 3671-2014-Lima) - Ariano Deho, Eugenia (2016)
This article provides a different approach to the debated issue of the criterion of solution of what has come to be called “property not registered vs. embargo registered”. In it, it argues that all the solutions that has been raised (even the adopted as “binding precedent” in the judgment of the Seventh Civil CassationPlenary) are based on an optical error, because they look at the embargo act of a static way, as if it were an act that creates a final situation, forgetting that the embargo is a procedural act that is not an end in itself, but is inserted into the dynamic of the execution process, a process in which the final situation occurs (the awarding of the asset under seizure to the successful bidder or creditor, that is, the acquisition of a real right). Observed, however, theembargo on the dynamic of the executive procedure, as an act that prepares the forced alienation of the asset, is postulated, as a criterion of solution to the problem, that of priority registration (that is, the contained in the first paragraph of the article 2022 of the Civil Code, but with the tempering of the appreciation of good faith), once the annotation of the embargo “reserve priority” to the act of forced alienation of the asset.